“Los instrumentos musicales y su incidencia en el desarrollo auditivo en el aula taller de la carrera de Educacion Parvularia de la Universidad Técnica de Cotopaxi en la parroquia Eloy Alfaro del cantón Latacunga de la provincia de Cotopaxi en el periodo 2012 - 2013” - Coro Cisneros, Norma Rocío (2013)
Teaching music to children was like a game. However, it represented a great stimulus to develop their skills and hone their abilities and sensitivity. That is, playing a musical instrument has many benefits for children, for this reason the instruments were classified by the way they are played and by the tone they generate with the purpose of generating an excellent musical environment. This research work was also based on the development of speech, language and hearing since they are an important part of the life of human beings. In speech, the ability to emit sounds was described, while language referred to the ability to understand and use these sounds. Hearing was necessary for the proper development of both speech and language. In the language it was mentioned that it is a basic instrument for the interpersonal relationship; and it was an act of communication that allows the exchange of ideas and emotions.